2017
DOI: 10.1016/j.pgeola.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

The Parallel Roads of Glen Roy, Scotland: geoconservation history and challenges

Abstract: Glen Roy is a classic geosite for ice-dammed lake shorelines, the Parallel Roads, and associated features formed during the Loch Lomond (Younger Dryas) Stade (12.9-11.7ka). The area played a key part in the development of the glacial theory in the early 19th century and continues today to have outstanding scientific value for understanding the processes and timing of events at the end of the last glaciation. Glen Roy has also been longappreciated as an awe-inspiring visitor attraction, and is now a flagship si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Geoconservation is the practice of conserving, enhancing and promoting awareness of those elements of geodiversity that have particular value (Prosser 2013a;Crofts & Gordon 2015). Historically, geoconservation in Scotland, and more widely in Britain, progressed in an ad hoc manner through the protection of a few emblematic sites during the 19th and early 20th Centuries in response to specific threats (Thomas & Warren 2008;Larwood 2016;Brazier et al 2017;Gordon et al 2018b). The development of modern geoconservation in Britain effectively began in the 1940s (Burek & Prosser 2008;Prosser 2013b), when the National Parks and Access to the Countryside Act (1949) first established a statutory basis for the systematic protection of biological and geological features of scientific interest within nature reserves and Sites of Special Scientific Interest (SSSIs).…”
Section: The Development Of Geoconservation In Scotlandmentioning
confidence: 99%
See 1 more Smart Citation
“…Geoconservation is the practice of conserving, enhancing and promoting awareness of those elements of geodiversity that have particular value (Prosser 2013a;Crofts & Gordon 2015). Historically, geoconservation in Scotland, and more widely in Britain, progressed in an ad hoc manner through the protection of a few emblematic sites during the 19th and early 20th Centuries in response to specific threats (Thomas & Warren 2008;Larwood 2016;Brazier et al 2017;Gordon et al 2018b). The development of modern geoconservation in Britain effectively began in the 1940s (Burek & Prosser 2008;Prosser 2013b), when the National Parks and Access to the Countryside Act (1949) first established a statutory basis for the systematic protection of biological and geological features of scientific interest within nature reserves and Sites of Special Scientific Interest (SSSIs).…”
Section: The Development Of Geoconservation In Scotlandmentioning
confidence: 99%
“…Some sites also have significant historical value in the development of geoscience and have played a major part in the development of key concepts and principles (Gordon & Barron 2011). Examples include Glen Roy, where the Parallel Roads and related features enabled Louis Agassiz to confirm his theory of continental-scale glaciation (Agassiz 1842;Brazier et al 2017), Agassiz Rock in Edinburgh, where Agassiz found evidence of glacial striations (Gordon 1993), the Forth valley, where Thomas Jamieson first developed the theory of glacial isostasy (Jamieson 1865), Rhu Point and Gare Loch, where Charles Maclaren noted the links between glaciation and raised shorelines and anticipating the concept of glacioeustasy (Maclaren 1842(Maclaren , 1846, the Cuillin Hills, where James Forbes (1846) presented one of the first detailed regional studies of glacial landforms in Britain including compelling evidence for the former existence of glaciers in the area and the role of glacial erosion in shaping the landscape, and the Hebrides, where W. B. Wright recorded the tilted nature of rock shorelines and originated the concept of shoreline diachroneity (Wright 1911(Wright , 1914(Wright , 1925. However, in both the UK and elsewhere, a number of wider values of geoheritage are being increasingly recognised (Crofts & Gordon 2015), and while scientific importance still remains the primary criterion, other factors are now being used to assess the value of geoheritage sites, including ecological, aesthetic, cultural and educational values and potential for geotourism (Reynard et al 2016;Brilha 2018a).…”
Section: The Wider Values Of Geoheritage and Geoconservationmentioning
confidence: 99%
“…History of geoconservation is also described in the study by Scottish scientists Vanessa Brazier, John E. Gordon et al "The Parallel Roads of Glen Roy, Scotland: geoconservation history and challenges." (Brazier, Gordon, Faulkner, Warner, Hoole and Blair, 2017); by the president of ProGEO José Brilha (Brilha, 2015); Ian Houshold and Chris Sharples "Geodiversity in the wilderness: A brief history of geoconservation in Tasmania" (Houshold, Sharples, 2008) etc.…”
mentioning
confidence: 99%